1977
DOI: 10.1017/s0022172400053080
|View full text |Cite
|
Sign up to set email alerts
|

Corynebacterium haemolyticum infections in Cambridgeshire

Abstract: SUMMARYIn the Cambridge area, 143 patients infected with Corynebacterium haemolyticum were found during the period May 1967 to December 1974. The pharynx was the commonest site of infection and 100 of the 137 pharyngeal infections were in patients aged between 15 and 25 years. Such patients usually had a sore throat; about half of them also had a maculopapular rash. The organism and the clinical features which we have come to regard as typical of this infection are briefly described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
2

Year Published

1981
1981
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 5 publications
(4 reference statements)
2
13
2
Order By: Relevance
“…After 48 h of incubation, a narrow zone of beta-hemolysis usually surrounds the colony and transmitted light reveals a small dark dot at the center of each colony. After a colony is gently pushed aside, the dot is left behind as a tiny dark pit in the agar (60,130,240 Kotrajaras and Tagami (109) are consistent with A. pyogenes. The A. pyogenes reaction with antisera against group G streptococci has been suggested as a simple test for distinguishing this organism from A. haemolyticum (10,112,113); however, commercial streptococcal reagents have not yet been tested against A. pyogenes.…”
Section: Fluorescent Diphtheroidsmentioning
confidence: 97%
See 3 more Smart Citations
“…After 48 h of incubation, a narrow zone of beta-hemolysis usually surrounds the colony and transmitted light reveals a small dark dot at the center of each colony. After a colony is gently pushed aside, the dot is left behind as a tiny dark pit in the agar (60,130,240 Kotrajaras and Tagami (109) are consistent with A. pyogenes. The A. pyogenes reaction with antisera against group G streptococci has been suggested as a simple test for distinguishing this organism from A. haemolyticum (10,112,113); however, commercial streptococcal reagents have not yet been tested against A. pyogenes.…”
Section: Fluorescent Diphtheroidsmentioning
confidence: 97%
“…The CDC does not have a single human isolate in their collection (87). Furthermore, as already mentioned, Jackman et al found that two of four human isolates received as C. bovis were, in fact, C. jeikeium; the other two were not further identified (93 (207,248); (ii) a report that it was a mutant of C. pyogenes (10); (iii) the description of a positive catalase test that is not observed with conventional testing methods (10); (iv) a major reference manual's statement (35) that most strains reduce nitrate to nitrite, which is not true of isolates from most regions of the world (45,60,80,110,176,240); and (v) the lack of hemolysis after 24 h on sheep blood agar, the medium used by >95% of clinical laboratories in this country. Nevertheless, A. haemolyticum can now be distinguished reliably from other coryneform groups on the basis of colonial morphology and conventional biochemical tests (45).…”
Section: Fluorescent Diphtheroidsmentioning
confidence: 99%
See 2 more Smart Citations
“…haemolyticum and S. aureus phage groups 1 and 2 have been reported to cause 'scarlet fever' (Fell, Nagington & Naylor, 1977;Feldman, 1961;Schlievert, 1981). There was no isolate of C. haemolyticum, and the three isolates of S. aureus did not belong to phage groups 1 and 2.…”
Section: Discussionmentioning
confidence: 99%